1983
DOI: 10.1093/jac/12.suppl_d.79
|View full text |Cite
|
Sign up to set email alerts
|

Comparative imipenem treatment of Staphylococcus aureus endocarditis in the rat

Abstract: The efficacy of imipenem alone or in association with gcntamicin against Staphylococcus aureus experimental endocarditis was compared to the efficacy of cloxacillin alone or in association with gentamicin. Parenteral treatment was started 24 h after intravenous bacterial challenge of rats with catheter-induced aortic valve vegetations. The cloxacillin MIC and MBC for Staph. aureus were 0-125 and 32 mg/1 and the imipenem MIC and MBC 0008 and 8 mg/1, respectively. In-vitro killing curves showed a synergistic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, incubation for 48 h revealed that the MIC was 50 ,ug/ml. I/C therapy was extended for another 2 weeks. Eleven days after discharge, the patient was readmitted with lumbar osteomyelitis due to MSSA.…”
Section: Resultsmentioning
confidence: 99%
“…However, incubation for 48 h revealed that the MIC was 50 ,ug/ml. I/C therapy was extended for another 2 weeks. Eleven days after discharge, the patient was readmitted with lumbar osteomyelitis due to MSSA.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the length of treatment (72 h) may have been too short. Studies with cloxacillin and imipenem showed that 5 days of treatment produced a more marked reduction in bacterial count in aortic valve vegetations than 3 days, while 10 days of treatment eliminated infection in most animals (2). Third, considering the relatively short half-life of these drugs in rats, the doses of CRO and NET may have been too low: for penicillin at least, the concentration should be maintained above the MIC throughout the dosing interval to prevent loss of efficacy as a result of bacterial regrowth (8,16).…”
Section: Discussionmentioning
confidence: 98%
“…In-vitro studies have reported high antimicrobial activity (Wise, Andres & Patel, 1981;Witte et al, 1982) of imipenem against methicillin-susceptible strains of S aureus and pharmacokinetic studies (Drusano, 1986;Wise et al, 1986) have shown that it is possible to achieve high levels in humans and animals, suitable for therapy of Gram-positive bacterial infections. In an experimental model of staphylococcal infection, namely aortic-valve endocarditis in rats (Baumgartner & Glauser, 1983) and rabbits (Apellaniz et al, 1991), the activity of imipenem was recorded as at least equivalent to that of the standard agent, cloxacillin, and even to that of cloxacillingentamicin combination therapy. Our results, which demonstrate significant imipenem activity against tissue cage infection by MSSA strain 120, agree with those previously reported for this antibiotic in both animals and humans.…”
Section: Discussionmentioning
confidence: 99%